Relationship between GDP and Productivity of G7 and BRICS countries in solid waste management research literature - M. Sabina; R. Jeyshankar (International Journal of Information Science and Management)
The primary aim of this study is to analyze whether developed (G7) or developing (BRICS) countries concentrate on Solid Waste Management (SWM) research. It also intends to associate and compare the productivity with the economic development of G7 and BRICS countries, productivity with world share performance, and measure the research profile of countries, which aids in strengthening the research areas' fund distribution and articulating suitable policy strategies. To examine this statement, the plain text files are exported to the software Bibexcel and MS Excel to determine the growth productivity of G7 and BRICS countries in SWM research, and scientometrics indicators such as activity index, relative specialization index are exploited to analyze the performance of the countries Mapping and visualization software like VOS viewer were utilized to identify the impact and contribution of top organizations. To analyze GDP and GDP per capita, the World Bank report has been involved. GDP and productivity of G7 and BRICS countries were compared and found an optimistic association between them with a 76% correlation. It reveals that both G7 and BRICS follow a linear growth model, and their performance is more remarkable than the average level with 0.98 of value. BRICS countries show a growing trend in publications compared to G7 countries, and the most prolific organizations are from China, which has the highest number of publications. It also received an excellent citation value of 44312, with the highest link strength of 18683 and a minimum of 4 cluster levels. The study concludes that developing countries focus more on SWM research than developed countries. Hence, developed countries can concentrate on SWM research, which aid to upsurge scientific production in upcoming years to progress the world's socio-economic development.